What Are the Potential Economic Benefits of Enlarging the Gulf Cooperation Council? - Elekdag, Selim (IMF Working Papers; Working Paper ;, 2004)
This paper uses a variant of the IMF's Global Economy Model (GEM) to estimate the macroeconomic effects of Yemen's full accession into the Gulf Cooperation Council (GCC). After calibrating the model to Yemen and the GCC countries, several simulations were carried out to estimate the potential impact of economic integration on both. The paper draws two fundamental conclusions. First, further steps in regional integration would enhance competition and produce large economic benefits for both Yemen and the GCC countries. In particular, we show that in some cases economic integration could increase GDP in Yemen by as much as 18 percent and in the GCC by as much as 20 percent over the long run. Second, even if market structures do not improve substantially, GCC enlargement can still generate substantial spillover gains with consumption increasing by up to 7 percent in Yemen and 8 percent in the GCC, respectively.